2015
DOI: 10.1080/13554794.2015.1023317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methylphenidate on sustained attention among adolescents with attention-deficit hyperactivity disorder

Abstract: Twenty-seven adolescents diagnosed as having attention-deficit hyperactivity disorder (ADHD) were tested twice with a computerized MATH-CPT (mathematics continuous performance test). In one administration, the participants took medication (methylphenidate, MPH) 1.5 hr before being tested. In another administration, the MATH-CPT was administered without the medication. Treatment with MPH improved the "overall attention level" and in measures of "reaction time" and "impulsivity." MPH did not improve the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…We found that MPH decreased misses and false alarms, and led to faster responses compared to placebo (Figure 3). These results replicate previous findings obtained with this dataset (Dockree et al, 2017) and others within the literature (Solanto, 1998; Spencer et al, 2009; Nandam et al, 2011; Bedard et al, 2015; Lufi et al, 2015). The beneficial effect of MPH could stem from its combined effect on both dopamine and noradrenaline, neuromodulators involved in cortical activation (Jones, 2005), sensory processing (Sara and Bouret, 2012) and motivation (Robbins, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…We found that MPH decreased misses and false alarms, and led to faster responses compared to placebo (Figure 3). These results replicate previous findings obtained with this dataset (Dockree et al, 2017) and others within the literature (Solanto, 1998; Spencer et al, 2009; Nandam et al, 2011; Bedard et al, 2015; Lufi et al, 2015). The beneficial effect of MPH could stem from its combined effect on both dopamine and noradrenaline, neuromodulators involved in cortical activation (Jones, 2005), sensory processing (Sara and Bouret, 2012) and motivation (Robbins, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…These effects were paralleled by stable subjective reports of sleepiness (Figure S1), meaning that participants did not experience the classical build-up of fatigue with time-on-task. These results replicate previous findings in this dataset (Dockree et al, 2017) and others within the literature (Bedard et al, 2015;Lufi et al, 2015;Nandam et al, 2011;Solanto, 1998;Spencer et al, 2009). The beneficial effect of MPH could stem from its combined effect on both dopamine and noradrenaline, neuromodulators involved in cortical activation (Jones, 2005) and motivation (Robbins, 1997).…”
Section: Sustained Attention Is Fine-tuned By Neuromodulatorssupporting
confidence: 90%